Chinese Medicine Syndrome Differentiation for Early Breast Cancer: A Multicenter Prospective Clinical Study - Guo, Qianqian; Coyle, Meaghan E.; Zhang, Anthony Lin; Xue, Xiaohong; Bian, Weihe; Song, Aili; Xie, Xiaohong; Hong, Ri; Lyu, Gang; Liu, Lifang; Chen, Qianjun; Xue, Charlie Changli (Frontiers in Oncology, 2022)
Background: Chinese medicine (CM) syndrome differentiation is one of the fundamental principles that guide the practice of Chinese herbal medicine (CHM). CHM has been widely used among breast cancer patients. Contemporary literature varies in syndrome diagnosis, and there is a need to standardize syndrome differentiation according to the different stages of breast cancer treatment. This multicenter clinical study aims to identify the CM syndromes and the clinical signs and symptoms in women with early breast cancer. Methods: Participants who met the inclusion and exclusion criteria were interviewed during the five treatment stages: preoperative, postoperative, chemotherapy, radiation therapy, and endocrine therapy. Patient demographic data and CM syndrome (as recorded by the treating CM clinicians in medical records) were gathered. Signs and symptoms were analyzed using descriptive statistics to derive the standardized CM syndromes using hierarchical cluster analysis. Results: The analysis included 964 interviews with 620 participants enrolled between 29 April 2020 and 30 May 2021 from eight participating hospitals in China. The two most frequent syndromes recorded in medical records were dual deficiency of qi and Blood, and dual deficiency of qi and yin during all but the preoperative stage. The symptoms of lassitude, lack of strength, and insomnia were common in all but the preoperative stage. Cluster analysis identified two clusters in the preoperative stage that most closely resembled the syndrome diagnoses of Liver stagnation with congealing phlegm, and dual deficiency of the Liver and Kidney. Two clusters—dual deficiency of qi and Blood, and dual deficiency of qi and yin—were common to multiple treatment stages. The syndrome cluster of Spleen and Stomach disharmony existed in both the postoperative and chemotherapy stages. Cluster analysis of the radiation therapy stage identified the unique syndrome of yin deficiency with fire toxin, while the endocrine therapy included the syndromes of Liver depression and Kidney deficiency. Conclusions: This multicenter clinical study showed consistency between results from cluster analysis and the most common syndromes recorded in the medical records. Findings from this clinical study will be further validated in a Delphi study to standardize CM syndromes for various stages of breast cancer treatment.